Gender-Based Differences in the Relationships Among Social Support, Positive Psychological Capital, and Sleep Quality in Patients Implanted With Pacemakers: A Moderated Mediation Model. Issue 1 (January 2022) - Lv, Gaorong; Zhao, Xiaojing; Xu, Xiaofang; Hou, Fangyan; Li, Ping
Abstract : Background: Sleep disorders are common and seriously affect the prognosis of patients implanted with pacemakers. Aims: In this study, it was investigated whether social support directly impacts sleep quality and whether positive psychological capital mediates and gender moderates the relationship between social support and sleep quality among this group. Methods: A total of 178 patients implanted with pacemakers were recruited to participate in the study from 2 tertiary hospitals in Shandong, China. Patients were assessed using the Perceived Social Support Scale, Positive PsyCap Questionnaire, and Pittsburgh Sleep Quality Index (PSQI). Multiple linear regression and the PROCESS macro were used to test the mediating and moderated mediating effects. Results: Patients' mean PSQI score was (8.48 ± 4.50), and 71.30% of the patients had sleep problems (PSQI > 5). Social support scores were negatively correlated with PSQI scores ( r = −0.19, P = .010) and positively correlated with positive psychological capital scores ( r = 0.45, P < .001). In addition, positive psychological capital scores were negatively related to PSQI scores ( r = −0.39, P < .001). The confidence interval (CI) from the bootstrap output indicated that positive psychological capital played a mediating role between social support and sleep quality (95% CI, −0.098 to −0.033), and gender moderated the association between social support and sleep via positive psychological capital (95% CI, −0.087 to −0.006). Conclusion: The sleep problems of this population cannot be ignored. Gender-based differences should be considered when guiding such patients toward using internal and external resources to cope with sleep problems.